CONTROL OF THREE-PHASE TWO-LEVEL AC/DC CONVERTER USING BACKSTEPPING CONTROL TECHNIQUE - Nguyen Thi Thanh Truc; Nguyen Thi Bich Hau (HUIT Journal of Science, 2025)
This paper presents a nonlinear control technique for a three-phase three-level AC/DC converter based on backstepping control. First, a non-linear model was applied in a rotating reference frame (dq). Then, the controllers for DC-link capacitor voltage and source current are designed, based on backstepping control theory. Based on the proposed control technique, the three-phase two-level AC/DC converter shows good performance, compared to the traditional PI controller. Simulation for three-phase two-level AC/DC converter using PSIM was performed to verify the proposed controller.